The characteristics of topeng klana udeng dance movements in tambi style using laban analysis - Farah Nurul Azizah; Nunung Nurasih; Desya Noviansya Suherman (Dewa Ruci: Jurnal Pengkajian dan Penciptaan Seni, 2026)
While previous studies on Indramayu mask dance have predominantly focused on visual fine arts or the Pekandanganstyle, empirical research systematically decoding the kinetic movement vocabulary of the Tambi style remains limited. To address this research gap, this study examines the movement characteristics of the Klana Udeng Mask Dance (Tambistyle) using an ethnographic framework integrated with an ethnochoreological approach and Laban Movement Analysis (LMA). Fieldwork was conducted through multi-angle video documentation, in-depth interviews with key practitioners, and Laban notation transcription. LMA findings reveal that the Tambi style is kinetically defined by a locked torso, wide open stance (pasang baplang), and sharp level variations, driven by an Effort combination dominated by direct space, strong weight, sudden time, and bound flow. These dynamic qualities generate assertive spatial Shapes and aggressive, martial-inspired (pencak silat) movement patterns that symbolize the authoritative and heroic nature of the Klana figure. The novelty of this research lies in providing the first standardized, count-scaled Laban notation and empirical Effort-Shape baseline for the Tambi stylistic tradition. Scientifically, this study demonstrates a replicable methodology bridging qualitative dance ethnography with formal choreological analysis. Practically, these findings offer a technical framework for curriculum standardization in local arts sanggars, cultural policy formulation, and Intellectual Property Rights (HKI) preservation for Indramayu’s intangible cultural heritage